Rukun Negara teras pembinaan modal insan: satu komentar - Lee, Yok Fee; Gill, Sarjit S. (Universiti Putra Malaysia Press, 2008)

(untitled)
In the process of achieving the status of a developed nation physically as well as spiritually by 2020, Malaysia is confronted by various complex issues. The issues come in various aspects, forms and levels like the moral issues, crime, ethnic relations, family, and the impact of globalization amongst others. In all the endeavours made by the government, the effort of human capital development can be considered spiritually and morally important. This agenda is significant in the formation of human capital with high quality and a first class mentality in the competitive era of globalization. Therefore, it is important to examine the effectiveness of all the human capital development efforts. The effectiveness of a policy very much relies upon the foundation that supports the policy to ensure its continuity. In line with this, this paper proposes that the national ideology, the Rukun Negara become the foundation of human capital development. It is expected that there will be problems in the integrated effort to inculcate the national ideology amongst Malaysians. Therefore, some challenges like the lack of monitoring system and the negative political influences will be discussed. Finally, several moderate proposals will be provided to strengthen the implementation of Rukun Negara towards the formation of human capital with a first class mentality and vision.